Investigation of the Static Nuclear Properties of Some Cr-Isotopes Using Skyrme-Hartree-Fock Method - Raheem, Ehsan M; Abdul Hasan, Ali A (Al-Nahrain Journal of Science, 2019)
The self-consistent Hartree-Fock (HF) calculations with several Skyrme parameterizations; SKM, SKM*, SLY4, SKxs25, MSK7, SKO, SKxta, and SKxtb have been used to investigate some static nuclear ground-state properties of some Chromium (50-54Cr) isotopes. The nuclear ground state charge, mass, neutron and proton densities with the corresponding root mean square radii, the charge form factors, the total binding energies and the neutron skin thickness can be calculated. The calculations are performed using NuShellX@MSU code, where the deduced results led to specifying one set or more of Skyrme parameterizations that used to achieve the best agreement with the available experimental data.